Adverse drug reactions related to methotrexate: a real-world pharmacovigilance study using the FAERS database from 2004 to 2024 - Liu, Siyu; Yuan, Zhang; Rao, Shicong; Li, Wenxing; Wu, Taiwei; Deng, Shuzhen; Zhong, Yongying; Lin, Jinyu; Guo, Wei; Yuan, Shiwei (Frontiers in Immunology, 2025)
ObjectiveTo comprehensively analyze the safety profile of Methotrexate in clinical use, clarify the incidence of adverse reactions and associated influencing factors, and provide evidence for safe medication practices in clinical settings.MethodsThis study retrieved data from the FDA Adverse Event Reporting System (FAERS) database from the first quarter of 2004 to the fourth quarter of 2024. Data filtering was conducted on the main suspect drug. Data extraction and cleaning were performed using R software, and various statistical methods, including ROR (Reporting Odds Ratio), PRR (Proportional Reporting Ratio), BCPNN (Bayesian Confidence Propagation Neural Network), and MGPS (Multi-Item Gamma Poisson Shrinker), were employed to detect adverse drug reaction signals. Subgroup analyses based on gender, age, and reporter categories were performed to explore differences.ResultsA total of 130,818 methotrexate (MTX)-related adverse event (AE) reports were included. Females accounted for 64.2% of reporters, with adults aged 18–64.9 years reporting the most. AEs primarily affected the immune, musculoskeletal, and hematologic systems. “General Disorders and Administration Site Conditions” was the most frequently reported system organ class [n=106,183, ROR (95% CI)=1.21 (1.21–1.22)], while “Immune System Disorders” showed the strongest signal [n=13,313, ROR (95% CI)=2.35 (2.31–2.39)]. Adverse reactions varied by gender and age: females were more likely to report Drug Hypersensitivity [n=6,192, ROR (95% CI)=4.69 (4.57–4.82)], while males reported Nausea more often [n=1,624, ROR (95% CI)=1.17 (1.12–1.23)]. Elderly patients (≥65 years) had an increased risk of drug hypersensitivity [n=2,894, ROR (95% CI)=7.91 (7.61–8.22)]. Reporting priorities differed: consumers frequently reported “Drug Ineffective” [n=5,729, ROR (95% CI)=2.24 (2.18–2.3)] and “Pain” [n=1,746, ROR (95% CI)=1.69 (1.61–1.77)], while healthcare professionals focused on DRUG INEFFECTIVE [n=9,982, ROR (95% CI)=4.16 (4.08–4.25)]. Additionally, the time to onset of MTX-induced AEs varied significantly across subgroups.ConclusionThis study reveals the safety characteristics of MTX in clinical use, confirms known adverse reactions, and identifies new potential adverse effects. It suggests that clinicians should enhance monitoring based on patient factors such as gender and age, particularly for immune system-related adverse reactions in elderly patients. Moreover, the spectrum of MTX’s side effects may be broader than previously recognized, warranting further research to ensure patient safety in drug use.